Kedudukan Hukum Surat Pencatatan Ciptaan Bagi Perlindungan Hak Cipta Karya Lukisan Dihadapkan Pada Prinsip Outomatically Protection - Wahyuni, Ridha; Ramadhani, Dwi Aryanti; Tarina, Dwi Desi Yayi (Universitas Ekasakti, 2023)
This researches aims to see the position of a creation registration letter of art painting as a form of legal protection for painting works in the face of the principle of automatic protection adhered to in Law no. 28 of 2014 concerning Copyright. The research method in this study is juridical-normative with an analytical descriptive approach. The results of the research show that a creation registration letter can be one of the perfect initial proofs if the painter as the creator will make efforts to protect the law against his work either through criminal law remedies and/or filing civil lawsuits. Therefore, the registration of creation through the registration of creation of a painting is important for every painter to obtain a creation registration letter from the state, this is an effort to protect their intellectual property rights.